Monetary theory and policy - Walsh, Carl E. (Cambridge, Mass. : MIT Press, 2003)
The book uses dynamic simulations to evaluate quantitatively the significance of the channels through which monetary policy and inflation affect the economy. It extensively examines modern approach to monetary policy that stress the incentives facing central banks and the strategic interaction between central banks and private sector.
Includes bibliographical references and indexes.
rpm 08/05/13
Loans
Keywords: Money; Monetary policy; Monetary theory